PSYCHOLOGICAL RESILIENCE OF MOUNT SINABUNG ERUPTION SURVIVORS IN NAMAN TERAN DISTRICT OF KARO REGENCY IN NORTH SUMATERA PROVINCE - Nuryanti Purba; Nazli; Marty Mawarpury (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
The community of victims of the Mount Sinabung eruption in the Naman Teran district of Karo Province of North Sumatra faces a major challenge to mental and emotional stability, experience of trauma, loss, and drastic changes in everyday life that can give profound psychological stress. Nevertheless, the communities in the Naman Teran district affected by the eruption of Mount Sinabung show resilience and ability to recover in coping with stress, trauma, and social psychological change in the community. The research aims to identify the factors that influence the resilience of the survivors of the Mount Sinabung eruption in Naman Teran District, Karo District, North Sumatra Province, Indonesia. The research uses a qualitative approach with data collection techniques through in-depth interviews, documentation, and participatory observations. The results show that there are several factors that influence the survivor’s resilience of the Mount Sinabung eruption, including social support, self-confidence, and adaptability. In addition, factors such as trauma, loss of property, and future uncertainty also affect psychological resilience. This research is expected to provide an innovative contribution to the development of volcanology-based natural disaster management programs that can improve the psychological resilience of the survivors of natural disasters.